Study of a single phase bridge fully controlled rectifier - Ling How Kiat (School of Electrical System Engineering, University Malaysia Perlis, 2011)
An electric power can be converted from one form to another form by usingpower electronics devices. The function of power electronics circuits by usingsemiconductor devices as switch is modifying or controlling a voltage. The goal ofpower electronics circuits are to convert electrical energy from one form to another,from source to load with highest efficiency, high availability and high reliability withthe lowest cost, smallest size and weight. The term rectification refers to the powercircuit whose function is to alter the ac characteristic of the line electric power toproduce a rectifiedac power at the load side that contain the dc value. In this projecttask, the rectifier circuit should be possible to produce a variable average voltage bycontrolling the delay angle. A versatile method of controlling the output of a full-wave rectifier is to substitute controlled switches such as thyristor for the diodes. The output is controlled by adjusting the delay angle of each thyristor.